STUDY REGARDING THE IMPORTANCE OF PARTICIPATION IN EXTRACURRICULAR ACTIVITIES ORGANIZED BY CENTRE FOR CAREER COUNSELLING AND GUIDANCE WITHIN UNIVERSITY OF AGRONOMIC SCIENCES AND VETERINARY MEDICINE FR - Ionuț PĂCURAR; Liviu MĂRCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Mobility is one of the aspects that define the current era, where distances are no longer a barrier both in terms of university studies and the possibilities of integration into the labour market or entrepreneurship. The skills acquired through extracurricular activities and digital skills are essential to have an easy path in professional development and access to a job focused on the field of university studies. The awareness of students and graduates regarding the accumulation of experiences from activities adjacent to the field of study and their sedimentation can bring them more personal and professional value. This paper aims to analyse the student perception and the importance of participation in extracurricular activities organized by The Centre for Career Counselling and Guidance (CCOC) for students and graduates of University of Agronomic Sciences and Veterinary Medicine (USAMV) from Bucharest in accordance with the rigors of the labour market. The research methodology involves the analysis of specialized literature regarding the extracurricular training activities that must be considered for the consolidation of a career in the studied field. The case study is composed of a questionnaire that contains 13 questions applied to USAMV Bucharest students and graduates. The resulting data were processed and analysed by statistical methods and the results obtained after interpretation give us an overall picture regarding the students/graduate’s awareness of the importance of extracurricular activities. However, the adaptation of activities must be a continuous process and the link between the university environment and the field companies should be strengthen for mutual benefits. Placing graduates in jobs that coincide with professional training remains a challenge. For this reason, a better understanding and application of the process of gaining professional experience during the higher education cycle is a key factor towards a successful career.